2021
DOI: 10.1155/2021/6551069
|View full text |Cite
|
Sign up to set email alerts
|

GPX4‐Regulated Ferroptosis Mediates S100‐Induced Experimental Autoimmune Hepatitis Associated with the Nrf2/HO‐1 Signaling Pathway

Abstract: Autoimmune hepatitis (AIH) is an inflammatory autoimmune disease of the liver. Oxidative stress triggered by reactive oxygen radicals is a common pathophysiological basis for the pathogenesis of many liver diseases, and ferroptosis is associated with the toxic accumulation of reactive oxygen species. The signaling transduction pathways responsible for iron processing and lipid-peroxidation mechanisms are believed to drive ferroptosis. However, the specific mechanisms regulating ferroptosis remain unclear. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The relationship between inflammatory progress and ferroptosis prompted us to investigate whether ferroptosis is involved in the development of autoimmune diseases [12]. In the S100-induced autoimmune hepatitis (AIH) mouse model, ferroptosis caused hepatitis by downregulating glutathione peroxidase 4 (GPX4), and was inhibited by the Ferrostatin-1 mediated Nrf2/ HO-1 signaling pathway [13]. Ferroptosis also exists in concanavalin A-induced AIH [14].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between inflammatory progress and ferroptosis prompted us to investigate whether ferroptosis is involved in the development of autoimmune diseases [12]. In the S100-induced autoimmune hepatitis (AIH) mouse model, ferroptosis caused hepatitis by downregulating glutathione peroxidase 4 (GPX4), and was inhibited by the Ferrostatin-1 mediated Nrf2/ HO-1 signaling pathway [13]. Ferroptosis also exists in concanavalin A-induced AIH [14].…”
Section: Introductionmentioning
confidence: 99%
“…Gpx4, a downstream gene of Nrf2, has been reported to inhibit the Nrf2 pathway to increase susceptibility to ferroptosis . Many studies have pointed out that ferroptosis can be reduced and that liver disease can be improved by activating the Nrf2 signaling pathway . Therefore, the present study further explored the mechanism by which GA alleviates SLI.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study showed that excess heme upregulated HO‐1 and promoted cardiac ferroptosis in mice with sickle cell disease 18 . HO‐1 mediated ferroptosis has been involved in the pathogenesis of multiple organ injuries, including myocardial infarction, 31 liver injury, 32,33 diabetis 34,35 retinal pigment epithelium degeneration, 36 and even cancer therapy 37 . Finally, heme‐assisted iron‐related oxidative reactions are associated with mitochondrial ROS and diverse metabolic processes, including heme catabolism in mitochondria, actively driving ferroptosis 23,38 .…”
Section: Discussionmentioning
confidence: 99%